Cosmetics Product and Self-Concept Among Senior High School Students: An Educational Perspective - Borling, Kenesha; Abraham, Elyza Criz; Pamplona, Chrissie Dyanne; Carbonell, Jims Adrian; Valdez, Anamarie (ASEAN Journal of Educational Research and Technology, 2023)
The study aimed to determine the significant relationship between Cosmetic Products on Self-Concept from an educational perspective. We used subjects from Sultan Kudarat State University - Laboratory Highschool Students. We used an adapted and modified questionnaire as the primary tool to gather data for this study. The Likert scale was used to determine the level of self-concept of the respondents when using cosmetics products and to what extent they use cosmetics products in different situations. The findings show that the respondents sometimes use cosmetic products in different situations, and the data revealed that the respondents have a high level of self-concept when applying cosmetics products. According to the respondents’ responses, cosmetics products and students’ level of self-concept has a high relationship. Recommendations have been made to conduct and that future researchers enhance the study by focusing on the large number of people who have a deeper understanding of the issue. We also recommend that the community should learn more about the self-concept of one person and they should give an understanding if even the young generation is more likely to use cosmetics to enhance their appearance.